The Utilization of Ang-Kak for Color in the Emulsion Fish Sausage - ถิระสาโรช จุฑามาศ; ถนอมวงค์ เฉลิมพล (KKU Science Journal, 2014)
Ang-Kak was used to improve color of emulsion fish sausage at 0.3, 0.6, 0.9 and 1.2 percent of fish weight. When compared with control containing 0.3 percent nitrite, it was found that the increasing amount of Ang-Kak resulted in with decreased LUX value (L*) and increased red value (a*). The addition of 1.2 percent Ang-Kak yielded the highest red value (a*) (p<0.05). On the other hand, the addition of 0.3 and 0.6 percent Ang-Kak yielded non-significant difference in firmness (p>0.05) when compared with the control sausage. The use of Ang-Kak showed no effect on moisture content, protein, and fat. However, the fish sausage with 1.2 percent Ang-Kak had the highest fiber content, pH, and overall acceptability, with significant moisture, and pH. The 1.2 percent Ang-Kak fish sausage contained standard level of microbials after 9 days of storage. difference (p<0.05) when compared to the control. After 12 days storage in polypropylene at 4 1 oC, control and 1.2 percent Ang-Kak added products tended to change in color, texture.